Filsafat Stoicism dan Relevansinya dengan Kebahagiaan Manusia: Studi Kebahagiaan Konsumtif dalam Dunia Digital Metaverse - Ma'arip, Muhammad Samsul; Hambali, Radea Yuli Ahmad (Jurnal Riset Agama, 2023)
This article aims to discusses the concept of happiness in the view of stoicism philosophy which explores consumptive happiness in digital metaverse technology which is now a hot issue discussed in the world. Happiness is a state of life and a condition of the heart that can give the impression of happiness and happiness in the view of stoicism that is often the most basic goal in life. In this study, as research material sourced from literature studies using library research and reviewing the description of the concept of happiness and analyzing consumptive happiness in the metaverse. But basically happiness is relative, but someone to be happy is the path of life's choice as a user of the metaverse itself. Regarding the findings in this article that the point of relevance of the concept of happiness in the philosophy of stoicism with happiness in this digital metaverse technology lies in happiness itself which is relative, where what is meant by happiness is relative here, it depends on the metaverse users themselves who are good at responding to situations. and conditions as described in the section on positive and negative impacts.